2017
DOI: 10.21608/edj.2017.76208
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between the Effect of Class Ii Amalgam and Composite Restorations in Posterior Teeth on Periodontal Tissues Health

Abstract: Aim of the study: To investigate and compare the effect of class II amalgam and composite restorations on periodontal tissues health. Materials & Methods: The gingival index, plaque index, probing depth and clinical attachment level of one hundred teeth (50 restored by class II amalgam filling and 50 restored by class II composite filling) were included in the present study. One hundred teeth were classified into two groups as follows: Group I: involved 50 teeth restored by class II amalgam filling. Group II: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The survival of dental amalgam is twice as high compared with composite filling, this is because of various factors like polymerisation shrinkage, deficient marginal adaptation, higher wear rates, defective contact points leading to food impactions, insufficiently converted composite at the bottom of the cavity are problems that cannot be underestimated when using resin-composite. 25,26,27 This does not imply that there is no weakness for amalgam: the need for retentive cavities at the cost of healthy tooth surface, weakening of tooth's strength by cutting through tooth's crown's ridges, the risk of fracture of remaining tooth substance as the result of cavity design and the lack of adhesion between amalgam and tooth substances. 28,29 The incidence of pocket depth more than 3mm in amalgam restorations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival of dental amalgam is twice as high compared with composite filling, this is because of various factors like polymerisation shrinkage, deficient marginal adaptation, higher wear rates, defective contact points leading to food impactions, insufficiently converted composite at the bottom of the cavity are problems that cannot be underestimated when using resin-composite. 25,26,27 This does not imply that there is no weakness for amalgam: the need for retentive cavities at the cost of healthy tooth surface, weakening of tooth's strength by cutting through tooth's crown's ridges, the risk of fracture of remaining tooth substance as the result of cavity design and the lack of adhesion between amalgam and tooth substances. 28,29 The incidence of pocket depth more than 3mm in amalgam restorations.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 However there are studies in which results indicated that class II composite restorations have more incidence of periodontal pocket compared to class II amalgam. 26,[32][33][34][35][36] The other studies may have used a different diagnostic criteria.. 26,[32][33][34][35][36] As the control in other studies were normal teeth without any restorations whereas the control in the present study were the teeth with class II restoration less than 3mm pocket depth. The comparison of pocket depth of pocket depth of more than 3 mm in between maxillary premolars and molars with a class II restoration, it was found that molars had more incidence of pocket depth more than 3 mm with 21 teeth than premolars with 10 teeth(Graph 4).…”
Section: Resultsmentioning
confidence: 99%
“…Many research studies were found in the literature that evaluates the effect of different restorative dental materials on periodontal health [20,[26][27][28][29][30]. However, no studies were found that appraise the effect of different service life (age) of class II amalgam restoration on periodontal health.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of a healthy periodontium is substantial for the long-term success of class II and V dental restorations. These restorations may affect periodontal health, if the distances between the junctional epithelium and supracrestal connective tissue attachment aren't respected, or in the presence of debris due to roughness of the surface, leading to gingival inflammation, connective tissue attachment loss and bone resorption (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Restorative resins, over time, have a greater degree of polish attainable but lack in strength and develop porosity. There is also an interaction between the resin and the organic compounds in toothpaste, plaque and soft drinks and there may be softening of the composite material or resin cement leading to surface roughness and plaque retention (10).…”
Section: Introductionmentioning
confidence: 99%